SCALP AND SHOOT FORMATION IN RESPONSE TO THIDIAZURON CONCENTRATIONS IN VITRO CULTURE OF PLANTAIN ‘TANDUK’ - Hapsoro, Dwi; Prayogi, Adi Noor; Ramadiana, Sri; Yusnita, Yusnita (JURNAL AGROTROPIKA, 2025)
This experiment aimed to study the formation of scalps and  banana shoots 'Tanduk' in vitro in response to thidiazuron (TDZ). Shoot explants measuring ± (1 x 1 x 1) cm3 were cultured in precondition media (MS+ 5 mg/l benzyladenine) for 4 weeks, then transferred to treatment media, namely MS + TDZ. This experiment was carried out using a completely randomized design with 3 replications and 7 treatments of TDZ concentrations (0.5; 1.0; 1.5; 2; 2.5; 3; 3.5; 4.0 mg/l).  Each experimental unit consisted of 5 bottles, each containing one explant. Observations of scalp number were carried out at 8 weeks of age. The scalps were subcultured on MS+5mg/l BA media to induce shoots. After 8 weeks in the shoot induction medium, the number of shoots was recorded.  The results showed that at 8 weeks on the culture all of the explants formed scalps, with the highest number of scalps (6 scalps/explant) was at 1 mg/l TDZ.  The scalp number decreased to 4.4 to 3.5/explant as the TDZ concentration increased from 1.5 to 4 mg/l. After 8 weeks on shoot induction media containing 5 mg/l BA, the highest number of shoots (3.8 shoots/explant) was obtained on the scalp from the 0.5 mg/l TDZ treatment. The shoot number decreased to (3.2-1.9/explant) with increasing TDZ concentrations from 1.0 to 4.0 mg/l.Keywords: Tanduk, plantain, thidiazuron, in vitro, scalp.